« Le plus passionnant et le plus original de tous les jeux » : les Treize de Georges Sim, par Détective (1929-1930) - Marie-Astrid Charlier (Criminocorpus)
Between March 1929 and June 1930, at the request of his friend Joseph Kessel, Georges Simenon published three series of thirteen short stories in Détective, under the pseudonym Georges Sim. Les Treize Mystères, Les Treize Énigmes and Les Treize Coupables are the subject of a "quiz" which calls the reader to solve each puzzle. For this, Détective sets up a vast play device that mixes texts and pictures/image. This device operates at different levels and is based on a vast set of tracks - true or false - that mixes related stories, intertexts, pictures/image and paratext. Also the playful circulation between these elements of the device does it result in multiple role plays: the reader is actor of the game, the magazine and Georges Sim are the authors while becoming characters, finally the images can be adjuvants or opponents as to the resolution of the plot.